Differences in the force-velocity profile between judoist and freestyle wrestlers - Párraga Montilla, J. A.; Latorre Román, P. A.; Serrano Huete, V.; Cabrera Linares, J. C.; Lozano Aguilera, E. D.; Jiménez Reyes, P. (Physical Activity Review, 2022)
Background: The aim of this study was to gain new knowledge about the force-velocity (F-V) profile in Judoist and freestyle wrestlers, investigating if there were any differences between sports and which physical demands have which fighting modalities. Participants: 24 athletes (male) took part in this study. Twelve Judoist (age: 20.3 ± 3.9 years, weight: 76.4 ± 10.4 kg; height: 179.4 ± 5.3 cm; BMI: 32.2 ± 1.9 kg/m2) and twelve freestyle wrestlers (age: 19.6 ± 4.5 years, weight: 65.3 ± 13.6 kg; height: 177.5 ± 5.7 cm; BMI: 23.8 ± 1.8 kg/m2) participated. Methods: To evaluate the F-V profile, the participants performed a squat jump (SJ) without load, as well as with different load conditions (0, 25, 50, 75, and 100% of athlete`s body mass). To assess the height of the jump, the OptoGait system was used. Consequently, the theoretical maximal force (F 0); the theoretical maximal velocity (V 0); maximal mechanical power output (Pmax); slope of the linear F-V relationship (Sfv); optimal F-V profile (Sfvopt ); and the differences between Sfv and Sfvopt (FV imb% ) were obtained. Results: A higher F 0 and lower V 0 were found in Judo athletes compared to wrestlers. Significant differences were found in Sfv and FV imb (p<0.001). Conclusion: The F-V profile is an accurate, reliable, and economical method that facilitates the evaluation of the current state of the athlete individua ly. Practical applications: The F-V profile method allows coaches and athletes to adjust their training objectives to achieve a higher level in their sport.